Peranan Lembaga Pemasyarakatan dalam Melakukan Pembinaan terhadap Narapidana Lanjut Usia - Aswar, Andi Kaisar Agung Saputra; Yasin, H. M. (Al-Ishlah: Jurnal Ilmiah Hukum, 2021)
The purpose of this study is to describe the role of Class II A Watampone Penitentiary in providing guidance and determine the factors that influence the part of the Class II A Prison in Watampone in giving direction to elderly prisoners based on Law No. 12 of 1995. This research was conducted at Class II A Watampone Penitentiary. This study uses an empirical approach to examine the efforts to develop elderly prisoners in Class II A Watampone Prison according to the reality in the field and is connected with the prevailing laws and regulations. This study's results indicate that the development of elderly prisoners at the Class II A Watampone Prison is in accordance with Law No. 12 of 1995 as the basic principle of all activities in LAPAS. Guidance for elderly prisoners is carried out through personality development and independence development. Patterns of personality development include fostering religious awareness, fostering national and state awareness, fostering intellectual abilities (intelligence), fostering legal awareness, fostering healthy reintegration with society, and fostering physical and spiritual health. The self-reliance pattern is given in the work service activity program by providing work skills based on groups that are determined and according to talents. The factors that influence the efforts to guide elderly prisoners in Class II A Watampone Prison, namely: facilities and infrastructure, human resources and other factors related to elderly prisoners.